2019
DOI: 10.24263/2304-974x-2019-8-4-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on chemical composition and antibacterial activity of fenugreek (Trigonella Foenum graecum L.) and cumin (Cuminum cyminum L.) seeds

Abstract: Introduction.The objective of this study was determination of the physico-chemical characteristics of fenugreek (Trigonella Foenum graecum L.) and cumin (Cuminum cyminum L.) and evaluation of their antibacterial properties against Staphylococcus aureus ATCC25923, Escherichia coli ATCC 25922 and Bacillus subtilis ATCC 6633. Materials and Methods. Different varieties of fenugreek and cumin were analyzed for their weight of 1000 seeds and germination rate. The physico-chemical analysis carried out was pH, titrata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…In previous studies about mineral composition of fenugreek plants, Bouhenni et al (2019) reported average Ca, K, Mg, P, S, B, Cu, Fe and Zn contents respectively as 1445, 10605, 1229, 5143, 2648, 11.8, 9.9, 91 and 30.9 mg/kg, Ali et al (2012) reported average Ca, Cu, Fe, Zn, K, Mg, P, Na and Mn contents respectively as 226, 5.4, 11.6, 4.4, 1080, 78.4, 200, 290 and 1.6 mg/100 g; Al-Jasass and Al-Jasser (2012) reported K, Mg, Ca, Zn, Mn, Cu and Fe contents respectively as 603, 42, 75, 2.4, 0.9, 0.9, 25.8 mg/100 g. Table 3. Fatty acid composition of the thousand-seed weight ranges Table 4.…”
Section: Mineral Compositionmentioning
confidence: 98%
“…In previous studies about mineral composition of fenugreek plants, Bouhenni et al (2019) reported average Ca, K, Mg, P, S, B, Cu, Fe and Zn contents respectively as 1445, 10605, 1229, 5143, 2648, 11.8, 9.9, 91 and 30.9 mg/kg, Ali et al (2012) reported average Ca, Cu, Fe, Zn, K, Mg, P, Na and Mn contents respectively as 226, 5.4, 11.6, 4.4, 1080, 78.4, 200, 290 and 1.6 mg/100 g; Al-Jasass and Al-Jasser (2012) reported K, Mg, Ca, Zn, Mn, Cu and Fe contents respectively as 603, 42, 75, 2.4, 0.9, 0.9, 25.8 mg/100 g. Table 3. Fatty acid composition of the thousand-seed weight ranges Table 4.…”
Section: Mineral Compositionmentioning
confidence: 98%
“…According to Bouhenni et al [25], Algerian variety of fenugreek (Trigonella foenum-graecum L.) and Syrian cumin (Cuminum cyminum L.) were the best ones, as compared to other varieties with a highest weight and a better germination rate. In this concept, these varieties were chosen for present study.…”
Section: Sample Preparationmentioning
confidence: 99%
“…The bactericidal activity of plant preparations against H. pylori significantly depends on the type of the extract and its components, concentration and exposure time and the density of the tested bacterial strains [ 47 ]. In previous studies, phytochemical screening of four plants was carried out and the results revealed the presence of eight phytochemical compounds in cumin extract, seven molecules in fenugreek extract, five compounds found in red onion extracts and one compound in garlic [ 32 , 33 ]. From these phytochemical studies, phenols are the largest group of metabolites in the studied plants and many compounds are believed to have remarkable anti- H. pylori effect in vitro and, to some extent, in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…Samples of garlic ( Allium sativum ) bulb, onion ( Allium cepa ) bulb, fenugreek ( Trigonella foenum-graecum L.) seeds and cumin ( Cuminum cyminum L.) seeds were sorted, washed and dried at room temperature, then ground into a fine powder and sieved through a 200 μm sieve. Resulting powders were used to prepare methanolic extracts using a maceration method; all the extraction procedures were performed and conditions were set as described by Bouhenni et al, (2019 a ) and Bouhenni et al, (2019 b ) [ 32 , 33 ]. Briefly, the methods applied to investigate the chemical composition of the tested plant extracts were:…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation